Dark matter - Michelle Paver (Orion Books, 2010)
What is it? What does it want? Why is it angry with me?' January 1937 Clouds of war are gathering over a fogbound London. Twenty-eight year old Jack is poor, lonely and desperate to change his life. So when he's offered the chance to be the wireless operator on an Arctic expedition, he jumps at it. Spirits are high as the ship leaves Norway: five men and eight huskies, crossing the Barents Sea by the light of the